2012
DOI: 10.1007/s11515-011-1181-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor receptor trafficking as a potential therapeutic target in pediatric cancer

Abstract: Growth factor receptors (GFRs) are often aberrantly expressed in tumor cells, and altered GFR expression and activity contribute to the pathogenesis of many types of cancer. A variety of mechanisms have been identified that result in enhanced GFR expression and activity in cancer cells. Defects in the pathways responsible for GFR internalization and intracellular trafficking are likely to be involved in altered GFR expression in a variety of cancers. The roles of GFR trafficking pathways in the regulation of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 129 publications
(159 reference statements)
2
11
0
Order By: Relevance
“…Aberrant GFR expression and function have been shown to be important in the pathogenesis of neuroblastoma. [25][26][27][28][29][30] We have observed that the UBE4B protein interacts with Hrs, a key regulator of EGFR endosomal trafficking and degradation, [31][32][33][34] and that the Hrs-UBE4B interaction is critical for efficient GFR trafficking and degradation, 14 suggesting that UBE4B expression and function may be associated with EGFR expression in neuroblastoma tumor cells. Therefore, we evaluated a cohort of 20 neuroblastoma tumor samples from the Children's Oncology Group (COG) for expression of UBE4B and EGFR proteins by quantitative Western blot analysis.…”
Section: Association Of Ube4b and Egfr Protein Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aberrant GFR expression and function have been shown to be important in the pathogenesis of neuroblastoma. [25][26][27][28][29][30] We have observed that the UBE4B protein interacts with Hrs, a key regulator of EGFR endosomal trafficking and degradation, [31][32][33][34] and that the Hrs-UBE4B interaction is critical for efficient GFR trafficking and degradation, 14 suggesting that UBE4B expression and function may be associated with EGFR expression in neuroblastoma tumor cells. Therefore, we evaluated a cohort of 20 neuroblastoma tumor samples from the Children's Oncology Group (COG) for expression of UBE4B and EGFR proteins by quantitative Western blot analysis.…”
Section: Association Of Ube4b and Egfr Protein Levelsmentioning
confidence: 99%
“…Deletions in the short arm of chromosome 1 (chromosome 1p36) are identified in approximately one‐third of neuroblastoma tumors and are associated with high‐risk tumor features and a poor prognosis 10‐12. The UBE4B gene is located in the 1p36 region and encodes an E3/E4 ubiquitin ligase 13, 14. Recently, Krona and colleagues identified a mutation in the UBE4B gene in the tumor from a patient with neuroblastoma with a fatal outcome 15.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulation of GFR trafficking is clearly emerging as an important mechanism for oncogenesis in a variety of human cancers. A large and growing body of evidence clearly demonstrates that disruption of the GFR trafficking pathways can alter cell expression and activity of GFRs, leading to the development and progression of cancer [38,39]. Therefore, developing a better understanding of the GFR trafficking pathways is critical in the understanding of the process of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%